2022
DOI: 10.3390/su14127446
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Impact of COVID-19 on Respiratory Muscles Structure and Functions: A Literature Review

Abstract: The impact of SARS-CoV-2 infection on respiratory muscle functions is an important area of recent enquiry. COVID-19 has effects on the respiratory muscles. The diaphragm muscle is perturbed indirectly due to the mechanical-ventilation-induced-disuse, but also by direct mechanisms linked with SARS-CoV-2 viral infection. In this sense, a deeper understanding of the possible links between COVID-19 and alterations in structure and functions of the respiratory muscles may increase the success rate of preventive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 105 publications
0
6
1
Order By: Relevance
“…[27][28][29] Mechanical ventilation can lead to disuse atrophy and muscle weakness in the diaphragm. [1] However, our study showed a different outcome: mechanical ventilation was not a predictor of intercostal muscle wasting during follow-up. The impact of mechanical ventilation on intercostal muscles remains uncertain, but we assumed that the relatively small number of patients who underwent mechanical ventilation might have influenced the results of our study.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…[27][28][29] Mechanical ventilation can lead to disuse atrophy and muscle weakness in the diaphragm. [1] However, our study showed a different outcome: mechanical ventilation was not a predictor of intercostal muscle wasting during follow-up. The impact of mechanical ventilation on intercostal muscles remains uncertain, but we assumed that the relatively small number of patients who underwent mechanical ventilation might have influenced the results of our study.…”
Section: Discussioncontrasting
confidence: 63%
“…Many individuals experience prolonged fatigue, muscle weakness, sleep disturbances, and mood disorders after recovering from COVID-19 pneumonia and subsequently encounter difficulties in having ordinary lives. [1][2][3][4][5][6] If various systemic symptoms and signs persist more than 3 months after SARS-CoV-2 infection and no other disease has been diagnosed, the World Health Organization defines this condition as post-COVID- 19.…”
Section: Covid-19 Was Declared a Pandemic By The World Healthmentioning
confidence: 99%
See 3 more Smart Citations